Secure Big Data Transmission based on Modified Reverse Encryption and Genetic Algorithm - Gaata, Methaq Talib; Ahmed, Zied O.; Ali, Rasha S. (Iraqi Journal of Science, 2023)
The modern systems that have been based upon the hash function are more suitable compared to the conventional systems; however, the complicated algorithms for the generation of the invertible functions have a high level of time consumption. With the use of the GAs, the key strength is enhanced, which results in ultimately making the entire algorithm sufficient. Initially, the process of the key generation is performed by using the results of n-queen problem that is solved by the genetic algorithm, with the use of a random number generator and through the application of the GA operations. Ultimately, the encryption of the data is performed with the use of the Modified Reverse Encryption Algorithm (MREA). It was noticed that the suggested algorithm provided more sufficient results concerning the key and the strength of security. However, it has lower computational efficiency as compared to the other algorithms.